A Critical Evaluation of the Role of a Geothermal System in Lithium Enrichment of Brines in the Salt Flats: A Case Study from Laguna Verde in the Atacama Region of Chile - Alam-, M (Elsevier Ltd, 2024)
The association between geothermal fluids and lithium-rich brines in salt flats has been evaluated in a unique natural laboratory in the Chilean Andes. The area encompasses Laguna Verde (LV), a hypersaline lake, and a salt flat (salar) within a closed basin surrounded by volcanoes. The predominant lithology consists of andesitic-dacitic rocks, with limited occurrences of rhyolitic rocks. The LV geothermal system exhibits surface manifestations, including over 20 hot springs reaching 47 °C along the lake s southern margin. The upflow zone is represented by the fumarolic field in the Nevado Ojos del Salado volcano, 25 km southwest of LV. Lithium concentrations range from 2.76 to 4.46 mg/L in thermal water and 0.59 to 0.76 mg/L in the Peñas Blancas river water, which feeds into LV after passing through a volcanic environment rich in lithium-bearing rocks. However, the thermal waters contribute over six times more lithium than non-thermal waters, highlighting their significance in releasing and transporting lithium from the source rocks to its eventual accumulation in LV. This natural laboratory at LV provides an excellent opportunity to evaluate the association between geothermal fluids and lithium-rich brines, offering valuable insights into the processes involved in lithium enrichment in similar geological and climatic conditions in other geographic areas. © 2024 Elsevier Ltd